Context encoder transfer learning approaches for retinal image analysis. (January 2023) - Morís, Daniel I.; Hervella, Álvaro S.; Rouco, José; Novo, Jorge; Ortega, Marcos
Abstract: During the last years, deep learning techniques have emerged as powerful alternatives to solve biomedical image analysis problems. However, the training of deep neural networks usually needs great amounts of labeled data to be done effectively. This is even more critical in the case of biomedical imaging due to the added difficulty of obtaining data labeled by experienced clinicians. To mitigate the impact of data scarcity, one of the most commonly used strategies is transfer learning. Nevertheless, the success of this approach depends on the effectiveness of the available pre-training techniques for learning from little or no labeled data. In this work, we explore the application of the Context Encoder paradigm for transfer learning in the domain of retinal image analysis. To this aim, we propose several approaches that allow to work with full resolution images and improve the recognition of the retinal structures. In order to validate the proposals, the Context Encoder pre-trained models are fine-tuned to perform two relevant tasks in the domain: vessels segmentation and fovea localization. The experiments performed on different public datasets demonstrate that the proposed Context Encoder approaches allow mitigating the impact of data scarcity, being superior to previous alternatives in this domain. Graphical abstract: Highlights: A transfer learning methodology on full-resolution eye-fundus images is proposed. 3 different approaches of Context Encoder are used as pre-training models. The evaluation is performed on vessels segmentation and fovea localization. The proposal mitigates the effect of data scarcity on neural networks. The proposal performance matches another outstanding transfer learning approach.